1995
DOI: 10.1002/j.1460-2075.1995.tb07285.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Drosophila Janus kinase (JAK) causes hematopoietic neoplasia and developmental defects.

Abstract: In mammals, many cytokines and growth factors stimulate members of the Janus kinase (JAK) family to transduce signals for the proliferation and differentiation of various cell types, particularly in hematopoietic lineages. Mutations in the Drosophila hopscotch (hop) gene, which encodes a JAK, also cause proliferative defects. Loss‐of‐function alleles result in lethality and underproliferation of diploid tissues of the larva. A dominant gain‐of‐function allele, Tumorous‐lethal (hopTum‐l), leads to formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
336
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(342 citation statements)
references
References 41 publications
6
336
0
Order By: Relevance
“…Luo et al (1995) showed that the dominant, gain-of-function mutation hop Tum-1 results from a single amino acid substitution at residue 341 and produces a clonal plasmacyte overproliferation similar to human leukemias. Similar studies by Harrison et al (1995) demonstrated that overexpression of wild-type hop or hop Tum-1 leads to an identical phenotype with tumor formation within the larval lymph glands, which serve as hematopoietic organs in Drosophila. The tumorigenicity of hop or hop Tum-1 overexpression was tissue speci®c, as expression in other tissues did not result in tumor formation.…”
Section: Inappropriate Stat Activation In Leukemiamentioning
confidence: 57%
“…Luo et al (1995) showed that the dominant, gain-of-function mutation hop Tum-1 results from a single amino acid substitution at residue 341 and produces a clonal plasmacyte overproliferation similar to human leukemias. Similar studies by Harrison et al (1995) demonstrated that overexpression of wild-type hop or hop Tum-1 leads to an identical phenotype with tumor formation within the larval lymph glands, which serve as hematopoietic organs in Drosophila. The tumorigenicity of hop or hop Tum-1 overexpression was tissue speci®c, as expression in other tissues did not result in tumor formation.…”
Section: Inappropriate Stat Activation In Leukemiamentioning
confidence: 57%
“…Constitutively active JAKs may be tumorigenic, at least in two settings. First, gain of function mutations in the Drosophila homolog of JAK, hopscotch, can cause tumors in¯ies, indicating that hyperactive JAKs may be oncogenes (Hanratty and Dearolf, 1993;Harrison et al, 1995). Second, a constitutively active form of JAK2, in form of the TEL/JAK 2 fusion product, has been identi®ed in chromosomal translocations found in atypical CML and pre-B cell ALL (Peeters et al, 1997).…”
Section: Biological Significance Of Jak Activation By V-ablmentioning
confidence: 99%
“…We have shown previously that overactivation of JAK, which phosphorylates STAT 5,6 , disrupts heterochromatin formation globally in Drosophila melanogaster 7 . However, it remains unclear how this effect is mediated and whether STAT is involved.…”
mentioning
confidence: 97%